Электроимпульсный погружной бур - Муратов В. М. Василий Михайлович; Лопатин В. В. Владимир Васильевич; Важов В. Ф. Владислав Фёдорович; Адам А. М. Альберт Мартынович; Дацкевич С. Ю. Сергей Юрьевич; Журков М. Ю. Михаил Юрьевич; Кураков А. Г. Андрей Григорьевич; Рёдланд А. Арильд
опубл. 10.03.13